Impact of two-close-frequency heating on ECR ion source plasma radio emission and stability. (27th August 2019) - Naselli, E; Mascali, D; Mazzaglia, M; Biri, S; Rácz, R; Pálinkás, J; Perduk, Z; Galatá, A; Castro, G; Celona, L; Gammino, S; Torrisi, G
Abstract: Experiments have recently demonstrated that kinetic instabilities occurring in magnetoplasma are huge limiting factors to the flux of highly charged ion beams extracted from ECR ion sources. Recently, it has been shown that the two-frequency-heating (TFH) mode has the proven potential to mitigate these instabilities. Since the fundamental physical mechanism of TFH is still unclear, a deeper experimental investigation is necessary. At ATOMKI-Debrecen, the effect on the kinetic instabilities of an argon plasma in a 'two-close-frequency heating' scheme has been explored for the first time by using a frequency gap smaller than 1 GHz (i.e. operating in the so-called two-closed-frequency heating mode). A special multi-diagnostics setup has been designed and implemented. In this paper, we will show the data collected by a two-pin, plasma-chamber immersed antenna connected to an RF detector diode and/or to a spectrum analyzer for the detection of plasma radio-self-emission when varying the pumping frequency in single versus double frequency heating mode. Data have been collected simultaneously to the beam extraction and for different frequency gaps and relative power balances. The turbulent regime of the plasma has been tentatively described in a quantitative way, according to the properties of the plasma self-emitted RF spectrum. The measurements show that plasma self-emitted radiation emerges from the internal ECR region everytime (i.e. below the lower pumping frequency) but the almost total instability damping can be effective for some specific combinations of frequency-gap and power balance, thus eventually improving the plasma confinement.